The journey of Texas community college DACA students through guts, resilience, initiative, tenacity - Redmond, Carolina (Kansas State University, 2022)
Undocumented children immigrants in the United States experience significant hurdles pursuing higher education due to their illegal status, resulting in lower rates of college attendance for children arriving before the age of 14 than U.S. born children. The 2012 Deferred Action for Childhood Arrivals (DACA) program aims, in part, to remove these barriers. In Texas, DACA recipients still face significant financial and other challenges, and some research has examined the role of guts, resilience, initiative, and tenacity (GRIT) in success for these students. However, it is not known which GRIT characteristics, if any, DACA students display or whether these characteristics influence access to community colleges or motivations to persist and complete college. The purpose of this qualitative phenomenological study was to explore the GRIT characteristics displayed in DACA students who attended a 2-year community college in Texas during the 2017 to 2018 academic semesters. Eleven DACA recipients meeting inclusion criteria completed the 8-Item Grit Scale Questionnaire and participated in interviews. Results revealed that all participants displayed all 4 elements of GRIT. Interviews yielded several themes: Participants displayed guts by declaring their immigration statuses, demonstrated resiliency by overcoming obstacles to college completion, used initiative to take advantage of opportunities, and remained tenacious in persevering despite financial and other challenges. Initiative was identified as the most influential characteristic created by participants’ desire to achieve goals and motivation from friends and family. More research is needed to further understand the potential benefits of GRIT for students’ success in higher education. However, the results indicate that GRIT can help DACA students be successful in higher education and may inform developing or improving programs to assist these students as they transition to community college.
Keywords: DACA; Guts; Resilience; Tenacity; Initiative; Community college